The Implementation School Culture in the Primary School Environment - Vevy Liansari; Niken Arien Syah Putri; Wulan Maulidyah; Novia Ramdhani B; Galuh Rismayati (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aims to describe the implementation of school culture implementation in elementary schools. The researcher used a qualitative. The data collection techniques used observation, interviews, and documentation. The results of the study are that the implementation of the school culture implementation program has been running well. This is proven by the existence of 8 school cultures including a clean culture, a culture of achievement, a religious culture, a culture of discipline, a culture of cooperation, a culture of politeness, a culture of responsibility, and an interest in reading. The efforts made are to find free time to hold meetings at least once a week and hold routine evaluation meetings every Saturday to discuss problems in one week implementation program has been running well. It proved existencing of 8 school cultures including a clean culture, a culture of achievement, a religious culture, a culture of discipline, a culture of cooperation, a culture of politeness, a culture of responsibility, and an interest in reading. The efforts made are to find free time for at least once a week to hold meetings and conduct routine evaluation meetings every Saturday to discuss problems in one week.